Predictors of internalised stigma among people with mental illness attending a psychiatry outpatient clinic in Ethiopia: Institution based cross sectional study - Wondale Getinet Alemu; Lillian Mwanri; Clemence Due; Telake Azale; Anna Ziersch (PLoS ONE, 2025)
Background Despite initiatives to increase access to mental health care and improve the quality of life for individuals living with mental illness, there is limited information on internalized stigma and its impact on these individuals. This study aimed to determine the prevalence of internalised stigma and identify associated factors (sociodemographic, clinical, and substance use) among people with mental illness attending an outpatient clinic in Ethiopia. Method Institution-based cross-sectional study was conducted with patients with mental illness at the University of Gondar Hospital clinic. We recruited 638 participants from the clinic using systematic random sampling with an interval of three applied. Internalised stigma was measured using the nine-item (ISMI-9) Internalised stigma of Mental Illness Scale. Variables were coded and entered into SPSS-28 software for further analysis. To analyze the data, we used descriptive and multivariate logistic regression analysis. Adjusted odds ratio (AOR) with 95% confidence interval (CI) and p-value less than 0.05 were considered significant. Results Prevalence of internalised stigma among study participants was 49.1% (95% CI: 45, 52). The following attributes were associated with a greater likelihood of high internalised stigma, participants with no formal education (AOR=2.19, 95% CI:1.33, 3.61); patients with fair self-reported health (AOR=3.12, 95% CI:1.28, 7.59), patients with poor self-reported health (AOR= 9.11, 95% CI: 2.89, 28.73), patients with suicidal ideation (AOR=1.95, 95% CI:1.37, 2.79), alcohol users (AOR= 1.89, 95% CI:1.24,2.91), patient with low self-esteem (AOR=1.55, 95% CI:1.09, 2.21), patient with poor drug adherence (AOR=2.2, 95% CI:1.30,3.71), patients with family history of substance use (AOR= 2.46, 95% CI:1.54,3.93). Conclusions The prevalence of high internalised stigma among patients with mental illness in was high. Therefore, anti-stigma activities, early outpatient support, drug adherence information, and reduction of suicidal behaviors are all necessary to reduce stigma in patients with mental illnesses.